Religion as a Source of Tolerance and Intolerance: Exploring the Dichotomy - Carlile, Alexandra (The international journal of religion and spirituality in society, 2020)
Previous research on tolerance and intolerance in religion has focused on individuals’ internal religious commitment and their relationship within religious groups. In exploring religion’s ability to generate both tolerance and intolerance, this qualitative study draws on data from interviews with 220 highly religious individuals living in the United Kingdom and Ireland in 2016 in order to suggest how religious individuals see themselves interacting with tolerance and intolerance in their daily lives. Many of our subjects identified themselves as tolerant people while viewing others as intolerant of their religious beliefs. An analysis of our findings and prior research suggests that religious intolerance is still a reality of current society but religious tolerance can be cultivated in environments of mutual understanding and communication.